Desperate Measures: How Teacher Preparation Programs can Engage and Retain Black Male Teacher Candidates - Black, Ernest; Rice, Ed (Educational (Re)naissance, 2020)
Black male teachers are less than two percent of all current teachers in the United States. However, there has been an effort to recruit and retain Black men into the teaching profession for a number of reasons. All student benefit when they have a Black male teacher. Black boys, in particular, have markedly higher test scores and improved discipline when they have a Black male teacher. Black male adults in educational settings is essential for enhancing Black boys’ academic and social development. There is a need for Black male teachers in education. Even with nationwide recruitment efforts like My Brother's Keeper, the numbers of Black male teacher remain small. Additionally, Black male teachers leave the profession at a higher rate than other subgroups. This paper will examine one teacher preparation program's effort to increase retention of Black males in the teacher preparation program and the teaching profession.